WOMEN IN THE WORLD TODAY - Escalante, Ana Cecilia; Camacho Monge, Daniel (Revista de Ciencias Sociales, 2023)
In this issue we present papers from the Feminist Meeting "Gender and Globalization in the Americas", held in April 2003 at the University of Costa Rica (UCR), organized by the Center for Latin American and Caribbean Studies (CELAC) and the Institute for Research on Women (IROW) of the State University of New York at Albany (SUNY-Albany), in conjunction with the Center for Research in Women’s Studies (CIEM) of the University of Costa Rica and the Feminist and Gender Studies Section of the Latin American Studies Association (LASA). The keynote address was given by Dr. June Nash, Distinguished Professor Emeritus of the Graduate Center, City University of New York and renowned Latin Americanist and feminist anthropologist. In this issue of the Social Science Journal, with the central theme of WOMEN IN TODAY’S WORLD, we publish Dr. Nash’s paper, "Women in the Middle: Globalization and the New Enlightenment".